1982
DOI: 10.1093/ije/11.4.368
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Acute Myocardial Infarction in Kuwait, 1978

Abstract: Two hundred and ninety-nine of 428 patients diagnosed with acute myocardial infarction (AMI) in Kuwait during 1978 were matched with hospitalized controls by sex, nationality, and same year of age. Patients were almost six times as likely as controls to be smokers (odds ratio [OR] = 5.6; 95% confidence limits [CL] = 2.8-12.3; P less than 0.0001) and 50% more likely to be diabetic (OR = 1.49; 95% CL = 0.96-2.32; P = 0.06). Patients were less likely than controls to be currently married (OR = 0.23; 95% CL = 0.04… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…Chronic diseases, and smoking-related diseases in particular, have become the main health problems in the Arab Gulf states, including Bahrain (Al-Owaish & Zack, 1982;Al-Roomi, Musaiger, & Al-Awadi, 1994;Al-Tamimi et al, 1996;Hamadeh, 1987;Hamadeh, & McPherson, 1993;Magrath & Litvak, 1993;Musaiger, 1994). Studies have shown that the prevalence of smoking in some of these countries is reaching an alarming level, especially in men (WHO, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic diseases, and smoking-related diseases in particular, have become the main health problems in the Arab Gulf states, including Bahrain (Al-Owaish & Zack, 1982;Al-Roomi, Musaiger, & Al-Awadi, 1994;Al-Tamimi et al, 1996;Hamadeh, 1987;Hamadeh, & McPherson, 1993;Magrath & Litvak, 1993;Musaiger, 1994). Studies have shown that the prevalence of smoking in some of these countries is reaching an alarming level, especially in men (WHO, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Although living standards have risen and health services in Kuwait have improved re markably in recent years, death rates from CHD and hypertension exceed those in some European countries [2], The control of these emerging cardiovascular health problems will require the control and modification of known and suspected CHD risk factors [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The coronary risk factors investi gated included: exercise performance; the cardiovas cular parameters (ECG, blood pressure and heart rates while resting and under maximum stress); an thropometric measures; blood lipid concentrations, cholesterol, high-density lipoprotein (HDL choles terol fraction, along with blood levels of triglycerides, glucose and uric acid; personal and family histories of coronary-related diseases; tension (presence or ab sence) socioeconomic factors, as applied previously [2,3], smoking habits and a number of composite fac tors, making a total of 26 variables included in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the prevalence of hypertension, diabetes, and high cholesterol in study of acute coronary syndrome in six Arab countries (Kuwait, Bahrain, the UAE, Yemen, Oman, and Qatar) was reported as 68%, 36%, and 63%, respectively. [ 12 13 14 ] Clinical epidemiology of MI in men and women has not been yet studied in Iran, one of the largest countries in Middle East, and no relevant report is available. This study was to determine the clinical epidemiology of MI in men and women in Iran.…”
Section: Introductionmentioning
confidence: 99%